2018
DOI: 10.1159/000491874
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibitor-Associated Tendinopathy and Muscle Tendon Rupture: Report of Three Cases of This Exceedingly Rare Adverse Event

Abstract: Aromatase inhibitors (AIs) are a commonly used antihormonal therapy in the treatment of breast cancer in postmenopausal women, specifically in the treatment of hormone receptor-positive breast cancer. AI-associated tendinopathy and muscle tendon rupture is exceedingly rare. Until now, only one case with AI-associated severe tendinopathy has been reported in the medical literature, and there are no recorded cases of AI-associated muscle tendon rapture. We report three cases of postmenopausal women with hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Barring the relationship between fluoroquinolone exposure and tendon disorder occurrence, exposure to statins, aromatase inhibitors, and glucocorticoids is also reportedly related to the occurrence of tendon disorders ( Marie et al, 2008 ; Laroche et al, 2017 ; Mitsimponas et al, 2018 ; Wise et al, 2012 ; van der Linden et al, 2002 ). In this cohort, we found that only patients who used statins were predisposed to developing tendon disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barring the relationship between fluoroquinolone exposure and tendon disorder occurrence, exposure to statins, aromatase inhibitors, and glucocorticoids is also reportedly related to the occurrence of tendon disorders ( Marie et al, 2008 ; Laroche et al, 2017 ; Mitsimponas et al, 2018 ; Wise et al, 2012 ; van der Linden et al, 2002 ). In this cohort, we found that only patients who used statins were predisposed to developing tendon disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Some systemic diseases, including cardiac disease, diabetes mellitus (DM), obesity, lipid disorders, and rheumatologic disorders have been reported in patients with tendon disorders ( van der Vlist et al, 2019 ). Moreover, tendon disorders are reportedly associated with the use of statins ( Marie et al, 2008 ), aromatase inhibitors ( Laroche et al, 2017 ; Mitsimponas et al, 2018 ), and glucocorticoids ( Wise et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to musculoskeletal adverse effects, aromatase inhibitors can be associated with tenosynovitis of the fingers, hands, and wrists in up to 50% of the treated patients. Rarely, aromatase-induced severe tendinopathy and rupture of larger tendons (such as the subscapularis, infraspinatus, and/or supraspinatus tendon) have occurred [ 1 - 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial management included discontinuation of the aromatase inhibitors. The two patients with ruptured tendons required surgical treatment; however, the woman with severe tendinopathy and no rupture had complete resolution of her symptoms within one month after replacing her drug and conservative treatment with corticosteroids [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These therapies can induce, for example, chondrocytes senescence and bone differentiation leading to osteoarthritis 40 . Furthermore, numerous other drugs are associated with the development of tendinopathies or muscle rupture 41,42 .…”
Section: Conditions Effecting Tendon and Ligamentsmentioning
confidence: 99%